(y-8)+24=3(y-6)

Simple and best practice solution for (y-8)+24=3(y-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (y-8)+24=3(y-6) equation:


Simplifying
(y + -8) + 24 = 3(y + -6)

Reorder the terms:
(-8 + y) + 24 = 3(y + -6)

Remove parenthesis around (-8 + y)
-8 + y + 24 = 3(y + -6)

Reorder the terms:
-8 + 24 + y = 3(y + -6)

Combine like terms: -8 + 24 = 16
16 + y = 3(y + -6)

Reorder the terms:
16 + y = 3(-6 + y)
16 + y = (-6 * 3 + y * 3)
16 + y = (-18 + 3y)

Solving
16 + y = -18 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
16 + y + -3y = -18 + 3y + -3y

Combine like terms: y + -3y = -2y
16 + -2y = -18 + 3y + -3y

Combine like terms: 3y + -3y = 0
16 + -2y = -18 + 0
16 + -2y = -18

Add '-16' to each side of the equation.
16 + -16 + -2y = -18 + -16

Combine like terms: 16 + -16 = 0
0 + -2y = -18 + -16
-2y = -18 + -16

Combine like terms: -18 + -16 = -34
-2y = -34

Divide each side by '-2'.
y = 17

Simplifying
y = 17

See similar equations:

| 15t+6t-11t=150 | | 7x-12x+31x+15x=+12-8 | | (x+59)+(x+51)+84=180 | | -12v+16=4(-3v+4) | | m+5-4=18 | | 5x-2=(14/3) | | 3/4b15 | | 11x-48=5x+10 | | 8n=87 | | 14-5(4f-6)=-3-17-20f | | 24a-22=4a(1-6a) | | 16x^3-12x^2+20x-15= | | 7x+2=7y-10 | | z-2.3=5.1 | | 2/5t=30 | | X^2+15x-160= | | 14s+3s-7s=200 | | 99+90+90+(x^2)=360 | | 4x+3x-x=+2-32+5 | | 3/5x-10=11 | | 2(-8m-16)=-4(4m+8) | | -y+13=-42 | | cos(x)cos(y)dx+sen(x)sen(y)dy=0 | | x^2=48x | | 4x-5(x+1)+=0 | | -y+13= | | 4(3z-12)+16=14z | | 12r+6r+2r=40 | | z/42=6/7 | | w=2xy+2zy | | 10-15y= | | -18=6+4w |

Equations solver categories